I spy spooky night : a book of picture riddles - Wick, Walter, 1953-; Marzollo, Jean; Marzollo, Dan; Marzollo, Dave (2019)
"Get ready to I Spy in a haunted house with lots of creepy riddles to solve!"--Publisher's description
Keywords: Picture puzzles -- Juvenile literature; Haunted houses -- Juvenile literature; Picture puzzles